Brecht at the opera - Calico, Joy Haslam, 1965- (California studies in 20th-century music, 2008)
'Brecht at the Opera' looks at the German playwright's lifelong ambivalent engagement with opera. The text argues that Brecht's simultaneous work on opera and 'Lehrstück' in the 1920s generated the new concept of audience experience that would come to define epic theater.